Handbook of Megachurches (Brill Handbooks on Contemporary Religion, 2019)
The megachurch is an exceptional recent religious trend, certainly within Christian spheres. Spreading from the USA, megachurches now reached reach different global contexts. The edited volume Handbook of Megachurches offers a comprehensive account of the subject from various academic perspectives. Readership: All interested in Christianity and contemporary religion, religious organisations, revivalism, and religion and popular culture.